A design of reconfigurable filtering-antenna for ultra-wideband applications - Al-Hegazi, Ammar Abdullah Hussein (2017)
Antenna is a main element in the UWB systems to transmit and receive signals. However, there are challenges to meet the requirements for a suitable UWB antenna compare to other narrowband antennas such as high data rate, omnidirectional radiation pattern and wide frequency bandwidth. Since the UWB technology is facing the interference problem with other narrow band signals such as WiMAX, WLAN and HiperLAN, which severely degrade the performance of the receiver in the UWB system, thus the conventional UWB system is integrated with bandstop filter in separated model from the antenna, which leads to increase complexity, cost, weight and loss. Therefore, researchers tend to integrate resonant structure in the antenna design to produce band notch characteristics and filter out unwanted signals using different techniques such as defected ground structure (DGS), defected patch structure (DPS) and resonant structure beside the feedline of the antenna design. However, the disadvantages of these techniques are the excessive band rejection, which rejects needed frequencies, and the fixed band notch whether the interfering signal exists or not, which may reduce the performance of the UWB system, thus producing sufficient and switchable band notch is a challenging issue to improve the performance of the UWB system. Therefore, in this research, a modified monopole antenna is designed to produce UWB bandwidth using microstrip transition in the feedline and block with triangular slot on each side of the circular patch. The modified monopole antenna is integrated with resonant structures to produce band notch characteristics and filter out unwanted signals. Two techniques based on defected microstrip structure (DMS) and two double split ring resonator (DSRR) are integrated with the antenna design individually. The DMS is embedded in the feedline of the antenna design to produce single band notch. The two DSRR are loaded above the ground plane of the antenna design to produce dual band notches. A PIN diode is employed in the resonant structure to achieve frequency reconfiguration. The results show that the modified monopole antenna exhibits wide bandwidth (129.5%) with a return loss better than -15 dB, high frequency skirt selectivity ranging from 3 to 14 GHz, which covers the entire UWB frequency band (3.1-10.6 GHz), peak gain of 5.3 dB and omnidirectional radiation pattern. The new integrations of filtering-antenna using DMS and DSRR provide stable omnidirectional azimuth pattern and sharp band notches, which are sufficient to remove unwanted signals and keep wanted signals. The simulated and measured results show a good agreement, where the proposed filtering-antenna using DMS exhibits wide bandwidth with switchable band notch at 5.5 GHz (WLAN), and the filtering-antenna using two DSRR exhibits wide bandwidth with switchable sharp band notches at 3.5 GHz (WiMAX) and 5.55 GHz (HiperLAN2).